Endevouridae, a review with description of four new species (Crustacea, Amphipoda, Lysianassoidea) - Lowry, James K.; Hughes, Lauren E. (Zootaxa, 2015)
The family Endevouridae is reviewed and four new species from the two genera, Endevoura and Ensayara, are described from Australian and Japanese waters. All species are diagnosed and the type species of Endevoura (End. mirabilis Chilton, 1921) and Ensayara (Ens. ramonella J.L. Barnard, 1964), respectively, are redescribed and illustrated. A key to the 19 known world species of Endevouridae is provided.